Temporal changes of circadian rhythmicity in cluster headache. (March 2020) - Lee, Mi Ji; Cho, Soo-Jin; Park, Jeong Wook; Chu, Min Kyung; Moon, Heui-Soo; Chung, Pil-Wook; Chung, Jae-Myun; Sohn, Jong-Hee; Kim, Byung-Kun; Kim, Byung-Su; Kim, Soo-Kyoung; Song, Tae-Jin; et al.
Objective: To investigate the temporal changes of circadian rhythmicity in relation to the disease course in patients with cluster headache. Methods: In this multicenter study, patients with cluster headache were recruited between September 2016 and July 2018. We evaluated the patients for circadian rhythmicity and time of cluster headache attacks in the current bout and any experience of bout-to-bout change in circadian rhythmicity. We analyzed the patterns of circadian rhythmicity in relation to the disease progression (the number of total lifetime bouts, grouped into deciles). Results: Of the 175 patients in their active, within-bout period, 86 (49.1%) had circadian rhythmicity in the current bout. The prevalence of circadian rhythmicity in the active period was overall similar regardless of disease progression. Sixty-three (46.3%) out of 136 patients with ≥2 bouts reported bout-to-bout changes in circadian rhythmicity. The most frequent time of cluster headache attacks was distributed evenly throughout the day earlier in the disease course and dichotomized into hypnic and midday as the number of lifetime bouts increased ( p = 0.037 for the homogeneity of variance). When grouped into nighttime and daytime, nighttime attacks were predominant early in the disease course, while daytime attacks increased with disease progression (up to 7th deciles of total lifetime bouts, p = 0.001) and decreased in patients with the most advanced disease course ( p = 0.013 for the non-linear association). Conclusions: Circadian rhythmicity is not a fixed factor, and changes according to the disease course. Our findings will be valuable in providing a new insight into the stability of functional involvement of the suprachiasmatic nucleus in the pathophysiology of cluster headache.